ANALISIS TINGKAT PENERIMAAN SISTEM INFORMASI KERUGIAN NEGARA/DAERAH (SIKAD) DI BPK RI - , Liza Haryani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Country/regional loss information system (is called SIKAD) is an instrument to obtain information on monitoring of the settlement of country/regional financial loss, and report about those cases fastly and effectively in BPK RI. During the deployment, 33% of the total of departement used SIKAD optimally, and 54% of data could be inputed to SIKAD from the total of state/region financial loss cases. This study aims to evaluate user acceptance of SIKAD in BPK RI. User in this study was inputer, a person who have duty to input the data of of country/regional financial loss. This study used Wixom and Todd model by adding social influence dan IT acceptance variable. Testing was conducted with Structural Equation Modeling (SEM) by using SmartPLS. Testing was started from validity dan reliability test, then hypothesis test in comparing t-statistic and t-tabel value at significant level 90%. The result showed that 8 (eight) hypothesis were accepted and had positive affect between variables, and 2 (two) hypothesis showed there were not positive affect between variables. Perceived of usefulness did not affect attitude toward using, and attitude toward using did not affect IT acceptance. Rejection of the hypothesis because the respondents think SIKAD could not facilitate their work and improve the effectiveness of their work. Recommendations that could be considered for the future among others provides easiness to inputer in performing taks and work, and IT Departement and Ditama Binbangkum efforts synchronization data source. Keyword - Country/regional loss information system, Wixom dan Todd Model, Social Influence, IT Acceptance, SEM.